2 dimensional computer modelling on flow in hydraulic turbine generator cooler - Chung, Jenn Chiu. (Universiti Malaysia Sarawak (UNIMAS), 2002)
Fouling represents an undesirable accumulation of deposits on heat transfer surface. Fouling is a consequence of various mass, momentums, and transfer phenomena involved with heat exchanger operation. The manifestations of these phenomena, though, are more or less similar. Fouling results in a reduction in thennal perfonnance and an increase in pressure drop in a heat exchanger. Two parameters that would most probably control any fouling process, the fluid flow velocity and heat transfer surface temperature, are examined in this study to identify the effect of these two factors on the fouling phenomenon. The results agree that generally, flow velocities do have some effects on the fouling process, based on the velocity profiles obtained and the pressure distributions. However, the temperature effect on the fouling in the cooler cannot be identified clearly. Finally, a closed circuit system is proposed to overcome the fouling problem in the cooler model. However, it is recommended that more extensive research should be conducted by concentrating on the physical and chemical properties of a fluid, the fluid and heat transfer surface temperatures; heat transfer surface properties and the geometry of the fluid flow passage should be given considerable amount of attention to obtain more accurate results.